Morphological and molecular analysis of Spinitectus notopteri (Nematoda: Cystidicolidae) from freshwater fish in Thailand - Kamchoo, Kanda; Hualkasin, Watcharasuda; Pathaburee, Pojchanad; Pachanawan, Adithepchaikarn (Folia parasitologica, 2024)
The nematode Spinitectus notopteri Karve et Naik, 1951 was collected from two species of freshwater fish belonging to the family Notopteridae, namely Chitala ornata (Gray) and Notopterus notopterus (Pallas), at Khun Thale Swamp in Surat Thani province of southern Thailand. The overall prevalence of the parasite was found to be 88% (94 fish infected/106 fish examined). A higher prevalence was found in C. ornata (96%), while a higher intensity was noted for N. notopterus (117 parasites/fish). The most important morphological characters were the presence of cephalic and cuticular structures, precloacal ridges, and genital papillae. Specimens were genetically characterised using cox1 mtDNA. Morphological characteristics were most similar to Spinitectus petterae Boomker, 1993 from Clarias gariepinus (Burchell) in Africa, while the genetic data were dissimilar to all available data for the genus. Therefore, the identification of nematode specimens using a combination of morphological and molecular techniques is stressed. This study also presents the first molecular analysis of S. notopteri infecting Thai freshwater fish and a new geographical record for S. notopteri.
Keywords: nemoci ryb; Notopterus notopterus; Phylogeny; Chitala ornata; Fish Diseases; ryby; molecular techniques; morphology; Nematoda; Thailand; zvířata; sladká voda; Thajsko; hlístice; infekce hlísticemi řádu Spirurida; Fishes; Nematode; cytochrome oxidase subunit 1 (cox1); Fresh Water; fylogeneze; Animals; Spirurida Infections